2017
DOI: 10.1111/trf.14393
|View full text |Cite
|
Sign up to set email alerts
|

Targeted exome sequencing defines novel and rare variants in complex blood group serology cases for a red blood cell reference laboratory setting

Abstract: Targeted exome sequencing resolved complex serology problems and defined both novel blood group alleles (CD55:c.203G>A, ABCB6:c.1118_1124delCGGATCG, ABCB6:c.1656-1G>A, and RHD:c.452G>A) and rare variants on blood group alleles associated with altered phenotypes. This study illustrates the utility of exome sequencing, in conjunction with serology, as an alternative approach to resolve complex cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 33 publications
0
49
0
1
Order By: Relevance
“…Many researchers have now shown that NGS or MPS can provide adequate coverage of the genes that determine blood group extended antigen typing in patients and donors. Schoeman and colleagues describe the first example of the use of NGS or MPS as part of the routine reference laboratory workup. The strength of this approach lies in the ability to potentially detect the relevant polymorphisms including null alleles, novel mutations, and complex gene rearrangements in blood group genes simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many researchers have now shown that NGS or MPS can provide adequate coverage of the genes that determine blood group extended antigen typing in patients and donors. Schoeman and colleagues describe the first example of the use of NGS or MPS as part of the routine reference laboratory workup. The strength of this approach lies in the ability to potentially detect the relevant polymorphisms including null alleles, novel mutations, and complex gene rearrangements in blood group genes simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Cost is a consideration, with the latest NHGRI data from July 2017 indicating a cost of $1121 to sequence an entire human genome . Exome sequencing, which targets only the coding region (exons), reduces cost and produces a smaller and more manageable volume of bioinformatics data, but as demonstrated by Schoeman and coworkers, the commercial exome library preparation they used did not target exons of all blood groups.…”
Section: Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Genomic DNA was extracted from ethylenediaminetetraacetic acid–whole blood tubes (EZ1 DNA Blood, QIAGEN). Blood group genomic sequencing, which included KEL and XK genes, was performed using a gene sequencing kit (TruSight One Panel, Illumina), as previously described . RefSeq KEL NG_007492.1 and XK NG_007473.2 were used for data analysis.…”
Section: Brief Methodsmentioning
confidence: 99%